Imperfect Price Information, Market Power, and Tax Pass-Through - Felix Montag; Robin Mamrak; Alina Sagimuldina; Monika Schnitzer (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
Pass-through determines how consumers respond to taxes. We investigate the impact of imperfect price information on pass-through of commodity taxes. Our theoretical model predicts that the pass-through rate increases with the share of well-informed consumers. Pass-through is higher for the minimum price, paid by well-informed consumers, than for the average price, paid by uninformed consumers. Moreover, pass-through to the average price is non-monotonic with respect to the number of sellers. An empirical analysis of multiple recent tax changes in the German and French retail fuel markets confirms our theoretical predictions. Our results have implications for tax policy and shed light on the relative effectiveness of Pigouvian taxes versus regulation.
Keywords: 330; pass-through; taxes; imperfect information; competition